2017
DOI: 10.1136/bmj.j2709
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, cognitive decline, and risk of dementia: 28 year follow-up of Whitehall II cohort study

Abstract: ObjectiveTo test the hypotheses that physical activity in midlife is not associated with a reduced risk of dementia and that the preclinical phase of dementia is characterised by a decline in physical activity.DesignProspective cohort study with a mean follow-up of 27 years.SettingCivil service departments in London (Whitehall II study).Participants10 308 participants aged 35-55 years at study inception (1985-88). Exposures included time spent in mild, moderate to vigorous, and total physical activity assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
282
6
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(314 citation statements)
references
References 45 publications
20
282
6
6
Order By: Relevance
“…Relative sedentary time was significantly higher in dementia patients than in controls (57% [49-68] vs. 55% [47-59], p = 0.042; Table 2). In addition, dementia patients spent a lower percentage of their waking time in light-to-moderate and moderate-to-vigorous intensity physical activity (20% [15][16][17][18][19][20][21][22][23] vs. 22% [18][19][20][21][22][23][24][25] and 5% [2][3][4][5][6][7][8][9][10] vs. 10% [5][6][7][8][9][10][11][12][13] Table 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative sedentary time was significantly higher in dementia patients than in controls (57% [49-68] vs. 55% [47-59], p = 0.042; Table 2). In addition, dementia patients spent a lower percentage of their waking time in light-to-moderate and moderate-to-vigorous intensity physical activity (20% [15][16][17][18][19][20][21][22][23] vs. 22% [18][19][20][21][22][23][24][25] and 5% [2][3][4][5][6][7][8][9][10] vs. 10% [5][6][7][8][9][10][11][12][13] Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…A decline in executive functioning (i.e., necessary for goal-directed behaviour, such as physical activity) could lead to apathy [22], which is known to lower activity levels in Alzheimer disease patients [23]. However, it is important to realize that lower physical activity and higher sedentary behaviour have already been reported in the preclinical stages of dementia [24] and in subjects with mild cognitive impairment [25]. This might suggest that differences in physical activity and sedentary behaviour are causally linked to progression from mild cognitive impairment to later stages of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that LoC may be an amenable target for interventions aimed at increasing internality, to improve cognitive function in adulthood and consequently, help to reduce risk of ageing-related morbidity (including Alzheimer’s disease, which has been consistently associated with lower cognitive function in mid-life and mortality [23,24]). Several studies have provided evidence that LoC is modifiable, with cognitive training interventions increasing internality [1517], and Nowicki et al [25] have identified several factors associated with changes towards both internality and externality.…”
Section: Discussionmentioning
confidence: 99%
“…internal to external and vice versa), supporting the assumption that it is not a static construct and may be amenable to intervention. Given that lower cognitive function in adulthood is associated with a lack of functional dependence in old age [26–28], greater risk of cognitive decline and dementia [23,24], and higher mortality rates [2932], identifying modifiable risk factors is important for informing prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study on the community-dwelling older adults reported that daily physical activity was associated with cognitive function variability in the elderly [20]. In addition, 28-year follow-up study analyzed using Whitehall II cohort reported that lower levels of physical activity was associated with an increased risk of dementia in the elderly [21].…”
Section: Discussionmentioning
confidence: 99%